Validation and Pilot Testing of a Guide to Measure the Costs Associated with the Management of COVID-19 and of Healthcare Associated Infections in Residential and Long-Term Care Facilities in Quebec - Tchouaket Nguemeleu, Eric; Robins, Stéphanie; Sia, Drissa; Létourneau, Josiane; Borgès Da Silva, Roxane; Kilpatrick, Kelley; Beogo, Idrissa; Parisien, Natasha; Boivin, Sandra (Science of Nursing and Health Practices / Science infirmière et pratiques en santé, 2021)
Introduction: As elsewhere in the world, Quebec (Canada) is currently facing the COVID-19 pandemic. Approximately 92% of deaths have occurred among people aged over 70, and approximately 100 long-term care (LTC) centers (termed CHSLDs in Quebec) were contaminated. This alarming situation is prompting stakeholders from healthcare networks to investigate the socio-economic repercussions of COVID-19. To the best of our knowledge, there is no valid and reliable tool to measure the costs associated with the management of COVID-19 in CHSLDs. Objectives: This research protocol aims to: i) adapt and validate for use in CHSLDs a combined guide, Cout-COVID19-SLD, developed from 2 guides used in acute care; ii) pilot the Cout-COVID19-SLD guide in CHSLDs and test its feasibility and afterwards resolve any barriers to its administration, and to conduct a partial estimate of costs brought about by COVID-19. Methods: A two-part prospective study will be conducted. Phase 1 will use a Delphi approach with 14 to 17 experts to validate the content of the Cout-COVID19-SLD guide. Phase 2 will pilot test the guide in a cross-sectional study in two CHSLDs. Discussion and conclusion: This study will provide a validated guide for the systematic measurement of costs associated with the management of COVID-19 (costs of preventive measures and costs of illness) in CHSLDs. Finally, this guide will serve as a valid and reliable instrument with which to better plan future research surrounding the socio-economic impacts of COVID-19 in CHSLDs.